1998
DOI: 10.1103/physrevlett.81.69
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Feshbach Resonance in Cold Atom Scattering

Abstract: We probe s-wave collisions of laser-cooled 85 Rb͑ f 2, m f 22͒ atoms with Zeeman-resolved photoassociation spectroscopy. We observe that these collisions exhibit a magnetically tunable Feshbach resonance, and determine that this resonance tunes to zero energy at a magnetic field of 164 6 7 G. This result indicates that the self-interaction energy of an 85 Rb Bose-Einstein condensate can be magnetically tuned. We also demonstrate that Zeeman-resolved photoassociation spectroscopy provides a useful new tool for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
236
1
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(246 citation statements)
references
References 25 publications
3
236
1
6
Order By: Relevance
“…For example, for systems interacting additively through Lenard-Jones potentials with well depth ǫ and length scale σ the coupling constant g is directly proportional to the atom mass, g = 4mǫσ 2 / 2 . As alluded to in the introduction, the coupling strength can be varied experimentally via a Feshbach resonance [30,31]. Although a full description of a Feshbach resonance requires the coupling between at least two channels-in tritium, e.g., of the singlet and triplet potential curves (coupled through a long-range hyperfine Hamiltonian) [10,32]-, some properties can be described within a single channel model.…”
Section: A Many-body Hamiltonianmentioning
confidence: 99%
“…For example, for systems interacting additively through Lenard-Jones potentials with well depth ǫ and length scale σ the coupling constant g is directly proportional to the atom mass, g = 4mǫσ 2 / 2 . As alluded to in the introduction, the coupling strength can be varied experimentally via a Feshbach resonance [30,31]. Although a full description of a Feshbach resonance requires the coupling between at least two channels-in tritium, e.g., of the singlet and triplet potential curves (coupled through a long-range hyperfine Hamiltonian) [10,32]-, some properties can be described within a single channel model.…”
Section: A Many-body Hamiltonianmentioning
confidence: 99%
“…The study of ultracold quantum gases is interlinked with controlling magnetic Fano-Feshbach resonances and thereby changing the effective interparticle interaction by many orders of magnitudes [1][2][3][4][5]. This makes ultracold Fermi gases a convenient tool to study the behavior of a degenerate fermionic many-body system [6] over a wide range of interaction strengths, in particular fermionic superfluidity [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…With dipole traps the trapping parameters are independent of externally applied magnetic fields. This property made possible the first observations of Feshbach resonances (29,30). It was shown that evaporative cooling was possible in dipole traps (31) and efforts were made to reach BEC in all-optical traps (31), but the original densities were too low.…”
Section: Advantages Of Optical Trapping and Cooling Techniquesmentioning
confidence: 93%